Guidelines for the diagnosis and treatment of testosterone deficiency (hypogonadism) in male patients with diabetes mellitus (Draft) - Galina Afanas'evna Melnichenko (Endocrinology Research Centre, 2017)
Hypogonadism in male patients is defined as a decrease in the serum testosterone level; it is associated with specific symptoms and/or signs (see the detailed description below). It is a common complication in diabetes mellitus. The guidelines do not review all disorders leading to the development of hypogonadism but focus on options for the treatment of hypogonadism, which is generally observed in male patients with diabetes. In the literature, data on the prevalence of hypogonadism in patients with diabetes are available. In the section on diagnostics, the medical history of patients with hypogonadism and diabetes, including the necessary methods for physical and laboratory inspection. Risk factors for and the clinical consequences of hypogonadism are separately considered. In the section on treatment options, variations in treatment using various androgenic therapeutic agents based on patients’ requirements, conservation of their reproductive function, and their risk factors are provided. Special attention is given to indications of, contraindications of and risk factors for androgenic therapy in male patients with diabetes, particularly those in their advanced age. The principles of the clinical monitoring are developed. The favourable effects of androgenic therapy for hypogonadism in male patients with diabetes are shown.